Strengthening Social Function of Land Rights to Achieve Justice and Community Welfare - Ati Yuniati; FX. Sumarja; Sepriyadi Adhan S; Keysa Bila Aldama (Universitas Kuningan, 2025)
The principle of social function of land rights in distributing agricultural land is major in promoting equitable land use and improving welfare of communities. Therefore, this study aimed to analyze how regulations on land sharecropping agreements are enforced and how social function of land rights is implemented. A socio-legal method was used by reviewing agrarian regulations and presidential instructions, combined with empirical, descriptive, and qualitative juridical data from in-depth interviews with 20 farmers and landowners. The study was conducted in Wono Agung Village, Tulang Bawang Regency, Indonesia. The results showed that regulations governing land sharecropping agreements were reviewed in agrarian regulations and enforced in presidential instructions. The implementation of social function of land rights showed that most sharecropping agreements were informal, without written documents or the presence of witnesses. The lack of a clearly defined duration rendered the agreements susceptible to unilateral termination. Although the sharecropping ratios largely followed the established provisions, namely maro 1:1 for rice and mertelu 1:2 for secondary crops, the calculation of cost was not comprehensive. A low level of community awareness of agrarian regulations had contributed to the continued dominance of customary law. This study assumed that the implementation of social function principle in Wono Agung Village, Tulang Bawang Regency, Indonesia, had not fully complied with formal provisions as well as the principles of agrarian justice. Additionally, the analysis recommended that sharecropping agreements be formalized in written contracts approved by the village head and witnesses. It also showed the need to improve agrarian legal literacy through intensive socialization. Local supervisory institutions should be required to oversee and evaluate the sustainable application of social function principle.